PELUANG HUKUM PIDANA ISLAM DALAM PEMBENTUKAN HUKUM PIDANA NASIONAL DI INDONESIA - Fitri wahyuni (Fakultas Hukum Universitas Islam Indragiri, 2018)
Islamic law is prescribed by Allah SWT with the aim of realizing and realizing and protecting the benefit of humanity, both for the benefit of individuals, society or both. But Islamic criminal law is not understood correctly and deeply by society, even by the Islamic community itself. in the meantime, the position of Islamic law in the field of civilization has been broadly established in positive law, whether it is an element of influence, or as a modification of religious norms, which are formulated in civil laws and regulations, or which are covered by a substantial legal environment. Law No. 7 of 1989 concerning religious justice. Whereas Islamic criminal law has not yet gotten a place like the positive law of Islamic civilization. Whereas Islamic criminal law has the same opportunities as civil law in the national legal system based on three factors, namely philosophy, sociology and juridical. In addition to the three factors above, there are opportunities described in this study so that Islamic criminal law has the opportunity to establish national criminal law in the future